Occupational ergonomics : theory and applications - Bhattacharya, Amit, 1946-; McGlothlin, James D. (Boca Raton, FL : CRC Press, 2012)
'Preface Since the publication of the first edition in 1996, significant new advances have been made in the field of ergonomics. These advances include the impact of aging and obesity in the workplace, the role of ergonomics in promoting healthy workplaces and healthy lifestyles, the role of ergonomic science in the design of consumer products, and much more. Therefore, we saw a critical need to update the first edition, which has had more than a dozen printings and can be found in libraries all over the world. We hope you agree that the second edition fills a critical gap between existing ergonomic books by providing a comprehensive approach that encompasses the principles of ergonomics from theory to practice. It also blends medical and engineering applications to solve musculoskeletal, safety, and health problems in a variety of traditional and emerging industries ranging from the office to the operating room to operations engineering. The scope and contents of this comprehensive book are such that it is suitable for graduate (and senior level undergraduate) students as well as a reference text for occupational safety and health professionals. This book is designed to address both the fundamentals of ergonomics (Part I) as well as practical applications (Part II) of those fundamentals in solving ergonomic problems to provide an insight into methods used to assess ergonomic risks and their control. Part III addresses the issue of connecting physical risk factors to the development of adverse health outcomes, thus providing a framework for the development of medical surveillance programs designed to monitor/control ergonomic-related challenges in the workplace'--
Includes bibliographical references and index.
Keywords: Human engineering; Industrial hygiene; Industrial safety; TECHNOLOGY & ENGINEERING / Engineering (General); TECHNOLOGY & ENGINEERING / Industrial Health & Safety; Human engineering; Industrial hygiene; Industrial safety